North of Portugal and Galicia (Spain) as tourism destinations: residents’ evaluation - Liberato, Dália (2020)
The dry border between the North of Portugal and Galicia presents structural, demographic and economic problems that must be overcome, but also natural, cultural and touristic resources that must be enhanced. From a more critical perspective, tourism must be discussed as an important strategic sector for the economy of Galicia-North of Portugal Euroregion and in particular, the dry borders’ economy, providing benefits, in a sustainable way. Border regions have been targeted areas for some EU-level investment interventions in order to allocate infrastructure and equipment considered key to boosting the territory, attracting investment in order to establish residents. The symbolic capital of this region lies precisely in its natural, architectural landscapes, as well as in several products in the region framed globally in endogenous resources. The aim of this research is to identify the potential for strategic cooperation between these two territories, and understand residents' perceptions about the impact of tourism, as an important economic activity, in these regions, through strategic partnerships between stakeholders and DMO’s, in the two countries, and also by valuing the border as a tourism destination, and not just as a line separating two territories and two nations.